1988
DOI: 10.1128/mcb.8.4.1803
|View full text |Cite
|
Sign up to set email alerts
|

Stably transmitted triple-promoter retroviral vectors and their use in transformation of primary mammalian cells.

Abstract: Retroviral vectors were constructed which coexpressed three inserted genes from independent transcriptional promoters in singly infected cells. Several such triple-promoter vectors were constructed with various combinations of oncogenes and selectable drug resistance genes. All expressed three mRNAs of the expected size in infected cells. One vector expressing the v-Ha-ras, v-myc, and neo genes was characterized in detail. This retrovirus did not undergo rearrangement during the process of infection, as judged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Therefore, we used dual-promoter lentiviral vectors. Although there were several studies reporting that dual-promoter vectors based on oncoretrovirus backbones showed severe reduction of transgene expression due to promoter interference (Emerman and Temin, 1984;Overell et al, 1988), a similar strategy was successful when using lentiviral vectors (Yu et al, 2003). Thus, Yu and colleagues have achieved efficient and consistent coexpression of two genes in cord-blood CD34+ HSCs or primary endothelial cells (Yu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used dual-promoter lentiviral vectors. Although there were several studies reporting that dual-promoter vectors based on oncoretrovirus backbones showed severe reduction of transgene expression due to promoter interference (Emerman and Temin, 1984;Overell et al, 1988), a similar strategy was successful when using lentiviral vectors (Yu et al, 2003). Thus, Yu and colleagues have achieved efficient and consistent coexpression of two genes in cord-blood CD34+ HSCs or primary endothelial cells (Yu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the cytoplasmic domain of TACE is not required for any of the shedding events examined and that the cysteine-rich domain of TACE is required for shedding of one of the substrates while affecting the inhibitor sensitivity of another substrate's shedding. (23). The resulting cultures were expanded, and clones were obtained by limiting dilution.…”
mentioning
confidence: 99%
“…The second approach involves expression of the upstream gene from the retrovirus promoter in the LTR and expression of the downstream gene from an internal promoter. This approach has been used most often in vectors designed for gene therapy (reviewed in references 28 and 34) but is compromised by competitive interference between promoters (4,8,20,39). Thus, individual isolates may express one gene or the other, rather than both.…”
mentioning
confidence: 99%